Implementation of Pancasila Values ​​in Overcoming Student Delinquency in Elementary Schools - Dinda Fransiski; Diah Sunarsih; Dedi Romli Triputra (Journal of Education Technology Information Social Sciences and Health, 2024)
Student delinquency is behavior or actions that can cause problems, which harm themselves or others. Student delinquency in Indonesia is still a serious problem, as many as 70% of students have committed delinquency, both minor and serious delinquency, which is caused by various factors, such as family, school and social environment. This research uses a qualitative approach, where data collection is carried out by interviews, non-participant observation and documentation. The main data sources in this research are class IV students, class V students, class IV teachers and class V teachers at SD Negeri Brebes 10. Meanwhile, supporting data sources in this research are taken from activity documentation, class journals and student report cards. The results of this research show the form of application of Pancasila values in overcoming student delinquency in elementary schools and the impact of applying Pancasila values in overcoming student delinquency in elementary schools. The application of Pancasila values including routine habituation activities, spontaneous habituation and programmed habituation in accordance with the first and third principles of Pancasila has been proven to be able to overcome student delinquency. These habituation activities also have an influence in forming the moral character of students, reducing acts of delinquency, increasing discipline and order, and strengthening social and emotional relationships among students.